2012
DOI: 10.1038/nrgastro.2012.123
|View full text |Cite
|
Sign up to set email alerts
|

Hepatopulmonary syndrome: update on pathogenesis and clinical features

Abstract: Hepatopulmonary syndrome (HPS) is a serious vascular complication of liver disease that occurs in 5-32% of patients with cirrhosis. The presence of HPS markedly increases mortality. No effective medical therapies are currently available and liver transplantation is the only established treatment option for HPS. The definition and diagnosis of HPS are established by the presence of a triad of liver disease with intrapulmonary vascular dilation that causes abnormal arterial gas exchange. Experimental biliary cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(122 citation statements)
references
References 161 publications
2
113
0
2
Order By: Relevance
“…It has been reported that HPS can increase the mortality of patients with liver cirrhosis, especially in those with severe hypoxemia 6,11,14,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that HPS can increase the mortality of patients with liver cirrhosis, especially in those with severe hypoxemia 6,11,14,19 .…”
Section: Discussionmentioning
confidence: 99%
“…It was also seen in both genders in middle-aged patients 17 . HPS pathogenesis is not well defined, but it is speculated that a combination of factors, such as an imbalance in the response of vascular endothelin receptors, pulmonary microvascular remodeling and genetic predisposition, leads to intrapulmonary vascular dilatation and bacterial translocation 1,10,12,14,17,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Today the term "hepatopulmonary syndrome" (HPS) describes deficiency of arterial oxygenation caused by dilatation of intrapulmonary vessels associated with liver disease [2][3][4][5]. A classification of the severity of HPS based on oxygenation abnormalities has been proposed [4] (table 1).…”
Section: Definition Prevalence and Classificationmentioning
confidence: 99%
“…This event could occur in portal hypertension, which will eventually result in intestines perfusion disturbance and increased rate of gram-negative bacteria and enteral endotoxin translocation. Moreover, it also induced the release of vasoactive mediators including NO [1,6,8,9].…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%